ARTISTIC INNOVATION AMONG CHINESE FIGURATIVE EXPRESSIONISTS: THE ROLE OF MOTIVATION, CULTURE, AND EMOTION - He , ShiFeng; Ismail , Adzrool Idzwan Bin (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Despite the global prominence of Chinese figurative expressionism, the psychological and cultural factors underlying artistic innovation in this genre remain underexplored. This study investigates how intrinsic Motivation, creative Climate, cultural Identity, and openness to Experience influence artistic innovation among Chinese figurative expressionist painters, with emotional Engagement and artistic Flow as mediators. Using a cross-sectional survey, data from 312 Chinese artists were analyzed with Partial Least Squares Structural Equation Modelling. Results show that intrinsic Motivation significantly predicts emotional Engagement (p < 0.001), artistic Flow (p = 0.007), and innovation (p = 0.002). Creative Climate significantly influences emotional Engagement (p = 0.005) and artistic Flow (p < 0.001) but shows a marginal direct effect on innovation (p = 0.054). Cultural Identity significantly predicts emotional Engagement (p = 0.037) and innovation (p = 0.003) but not Flow (p = 0.324). Openness to Experience significantly predicts emotional Engagement (p = 0.028), Flow (p < 0.001), and innovation (p = 0.017). Emotional Engagement (p = 0.002) and artistic Flow (p = 0.001) directly enhance innovation. Mediation analyses reveal that emotional Engagement mediates the effects of intrinsic Motivation (p = 0.014), creative Climate (p = 0.046), and cultural Identity (p = 0.047) on innovation. Artistic Flow mediates the effects of creative Climate (p = 0.010) and openness to Experience (p = 0.013) on innovation. These findings highlight the roles of psychological traits, socio-cultural context, and affective states in fostering innovation among Chinese painters and provide a framework for enhancing creativity through intrinsic and contextual factors. JEL Classification Codes: C12, C20, C31.